Online Measurement on Flatness and its Uncertainty of Small Work-piece - LI Guihua; ZHANG Huajun; MA Xiushui (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Flatness is a very important shape and position of plane surface error and has great influence on the operating function of the work-piece. The traditional measurement methods of flatness can not be satisfied with the real-time requirement, and the uncertainty of flatness is not easy to be evaluated either. So a new method is proposed based on Geometrical product specification (GPS) standard-chain. That is: the coordinate value of small work-piece is occurred by portable Coordinate Measure Machine (CMM), the flatness is calculated from these coordinates using least-square arithmetic, and the uncertainty of flatness is estimated by the experimental matrix. The qualified products are separated by the tolerance and the agreement of supply and demand sides, and all the results are shown in an interface in real-time. Random inspection shows that this method can realize to pick the rejects online, increase the measurement efficiency, and decrease the probability of misconstruction. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2083